2022
DOI: 10.3390/agronomy12112764
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Selection of Processing Process and Parameters of Platycodon grandiflorum Seeds Assisted by Machine Vision Technology

Abstract: Seed processing is an important means of improving seed quality. However, the traditional seed processing process and parameter adjustment are highly empirically dependent. In this study, machine vision technology was used to develop a seed processing method based on the rapid extraction of seeds’ material characteristics. Combined with the results of clarity analysis and the single seed germination test, the seed processing process and parameters were determined through data analysis. The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…They differ from modern methods in several ways. According to Wu et al [10], in traditional methods, seed processing is highly empirically dependent, with parameters adjusted based on experience while modern methods utilize machine vision technology for rapid analysis and determination of processing parameters. Another study by [11] showed that traditional seed production and processing techniques involve manual or mechanical emasculation and male gametocide chemicals, while modern methods utilize biotechnological approaches such as genetic means of male sterility and genomics-assisted breeding.…”
Section: Introductionmentioning
confidence: 99%
“…They differ from modern methods in several ways. According to Wu et al [10], in traditional methods, seed processing is highly empirically dependent, with parameters adjusted based on experience while modern methods utilize machine vision technology for rapid analysis and determination of processing parameters. Another study by [11] showed that traditional seed production and processing techniques involve manual or mechanical emasculation and male gametocide chemicals, while modern methods utilize biotechnological approaches such as genetic means of male sterility and genomics-assisted breeding.…”
Section: Introductionmentioning
confidence: 99%